2016
DOI: 10.1016/j.jcin.2016.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Does Residual Thrombus After Aspiration Thrombectomy Affect the Outcome of Primary PCI in Patients With ST-Segment Elevation Myocardial Infarction?

Abstract: STEMI patients with greater residual thrombus burden after aspiration thrombectomy had worse microvascular dysfunction and greater myocardial damage compared with those with smaller residual thrombus burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 26 publications
0
32
0
4
Order By: Relevance
“…In the ESC guideline (2017), routine thrombus aspiration is not recommended 19) . As it was reported that STEMI patients with a greater residual thrombus burden after aspiration thrombectomy had worse microvascular function and larger myocardial damage than patients with a smaller residual thrombus burden 20) , thrombectomy should be chosen carefully. In the present case, we repeated thrombus aspiration, but could not remove the blood clot effectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the ESC guideline (2017), routine thrombus aspiration is not recommended 19) . As it was reported that STEMI patients with a greater residual thrombus burden after aspiration thrombectomy had worse microvascular function and larger myocardial damage than patients with a smaller residual thrombus burden 20) , thrombectomy should be chosen carefully. In the present case, we repeated thrombus aspiration, but could not remove the blood clot effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that intracoronary thrombi can lead to micro- and macro-vasculature embolization and is associated with poor outcomes in patients who underwent PPCI of culprit lesion. 6 - 8 However, management of thrombotic burden is still challenging during PPCI for STEMI. Early risk stratification to detect patients at high risk of high thrombus burden is very important for the individualized prevention and treatment of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombus aspiration is an adjunctive non-pharmacological strategy during primary PCI designed to improve epicardial and myocardial reperfusion. However, recent studies failed to show the clinical benefit of aspiration thrombectomy in STEMI patients due to insufficient removal of thrombus at the culprit lesion [19][20][21].…”
Section: Optimal Lesion Preparation For Dcb Applicationmentioning
confidence: 99%